Simulation of thin films delamination under compression - Kurguzov, Vladimir Dmitrievich (Computational Continuum Mechanics, 2014)
Processes of elastic deformation of thin films under mechanical loading conditions are considered. A film is modeled as a longitudinally compressed beam with a small-area of initial delamination of the film from the initial film carrier. The compressive buckling problem of a beam partially fixed on the elastic foundation is solved. Bending strains of the beam are considered to be small; therefore the approximate differential equation of the bending line of a beam is used. The gluing conditions for the solution of both the delaminated beam and the beam on the elastic foundation have been defined. The post-buckling behavior of the “beam - foundation” system has been studied. The forms of beam buckling within the constant factor have been derived when exceeding the Euler critical loading by a compressive force takes place. Comparison of the proposed deformation model of a beam partially glued on the elastic foundation with the numerical solution of the buckling problem of a thin plate fixed on the elastic foundation obtained in the geometrically nonlinear statement by the finite element method shows the qualitative agreement between these solutions. The computer simulation shows a possibility for progressive delamination of a thin film from the film carrier when exceeding a critical loading. In contrast to the currently available approaches, the proposed one takes into consideration the elastic strain of a film carrier that provides the relationship of critical bending stress versus foundation stiffness.